1994
DOI: 10.1111/j.1432-1033.1994.tb18877.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐induced synthesis and tunicamycin‐sensitive secretion of the putative storage glycoprotein conglutin γ from mature lupin seeds

Abstract: ) -E.IB 94 0179/1 SDSRAGE, inmune blotting with specific antibodies and amino acid sequence analyses revealed that 90% of the protein released from Lupinus albus seeds incubated in water at 60°C for about 3 h was conglutin y , a putative storage glycoprotein already present in the protein bodies of mature seeds. Incorporation of ['4C]leucine into the protein demonstrated that conglutin y was newly synthesized during the treatment and the use of protein synthesis inhibitors ruled out the secretion of constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 41 publications
4
40
0
Order By: Relevance
“…In the present study, the α- and β-conglutins were successfully separated from the total globulin fraction by anion exchange chromatography. Since the amount of γ-conglutin obtained by this procedure was small, a heat treatment of the lupin seeds was performed [32,] resulting in sufficient amounts of the protein for subsequent studies. Furthermore, the isolated globulin fractions corresponded in their molecular size to those reported by others [24, 31, 32, 36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the α- and β-conglutins were successfully separated from the total globulin fraction by anion exchange chromatography. Since the amount of γ-conglutin obtained by this procedure was small, a heat treatment of the lupin seeds was performed [32,] resulting in sufficient amounts of the protein for subsequent studies. Furthermore, the isolated globulin fractions corresponded in their molecular size to those reported by others [24, 31, 32, 36].…”
Section: Discussionmentioning
confidence: 99%
“…The release of γ-conglutin was induced by the heat treatment of mature L. angustifolius seeds as described in the literature [32]. In brief, dry seeds were soaked in deionized H 2 O (1:10 w/v) and heated for 4 h at 60°C under gentle shaking.…”
Section: Methodsmentioning
confidence: 99%
“…Like Bg, conglutin and carrot XEGIP bind insulin and leginsulin 2,17,22) and thus may be involved in signal transduction. Both conglutin and carrot XEGIP are synthesized in the responses of plants to abiotic stresses (heat treatment 23) and mechanical wounding 24) ). It would be interesting to test whether Bg and conglutin retain any residual xylanase inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a general protective role of XEGIP against biotic or abiotic stresses can be assumed, based on its wide expression in tomato vegetative tissues and high expression in cultured cells (Qin et al 2003). Leguminous seed proteins Bs7s and Cg have been considered as storage proteins, but more recent research indicates an additional physiological role as enhanced expression is observed in the response to heatshock (Duranti et al 1994;Kagawa and Hirano 1987) and both proteins have the capacity to bind specific proteins or peptides (Komatsu and Hirano 1991;Duranti et al 1995). Chromosomal location of TAXI-like genes PCR on nulli-tetrasomic lines located the identified TAXI-I sequence on wheat chromosome 3B of cv.…”
Section: Identification Of Taxi-like Genesmentioning
confidence: 99%